Implementasi Ekstrakurikuler Pramuka Dalam Membentuk Karakter Akhlak Mulia Di MTS Negeri 2 Deli Serdang - Zahraini Husna Lubis; Pan Su’aidi; Yulia Warda (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to analyze the implementation of Scout extracurricular activities in shaping students' noble character at MTs Negeri 2 Deli Serdang, as well as the implications, supporting factors, and obstacles. The research used a qualitative approach with in-depth interviews involving Scout instructors, Akidah Akhlak teachers, the principal, vice principal, and students. The results show that Scout extracurricular activities effectively integrate noble character values into students’ real-life experiences, supported by school policies and systematic guidance. Positive implications include improvements in individual attitudes and the quality of the school’s social environment. Supporting factors include student enthusiasm, instructor support, and school policies, while obstacles involve limited time, student fatigue, and technical constraints. The study recommends enhancing instructor training and better time management to optimize noble character development through Scout activities